Maternal Hemodynamic Responses to Epinephrine-Containing Local Anesthetics in Mild Pre-Eclampsia. Issue 3 (July 1988) - Dror, A.; Abboud, T. K.; Moore, J.; Swart, F.; Mosaad, P.; Davis, H.; Gangolly, J.; Mantilla, M.; Makar, A.; Zaki, N.
Abstract : This study was undertaken to determine the maternal hemodynamic responses to epinephrine added to local anesthetics during lumbar epidural anesthesia for labor in 30 mildly preeclamptic patients. Group I (n=16) received 1.5% lidocaine with 1:200, 000 epinephrine and group II (n=14) received plain 1.5% lidocaine in a double-blind randomized fashion. Parameters recorded included maternal blood pressures and heart rates, fetal heart rates, duration of analgesia, and neonatal outcome. None of the patients in group I developed hypertension after administration of lidocaine with epinephrine, and they had significant decreases in their mean systolic and diastolic blood pressures compared with baseline values ( P <0.05). No significant changes were observed in group II patients. Duration of anesthesia was significantly ( P <0.01) longer in group I (102.5 ± 6.5 minutes) compared with group II patients (55.7 ± 5.4 minutes) (mean ± SEM). All neonates had normal fetal heart rate patterns and had Apgar scores of 9 or more at 5 minutes. Results from this study suggest that mildly pre-eclamptic patients are not likely to experience hypertension when small amounts of epinephrine are injected epidurally.